2017
DOI: 10.3892/mmr.2017.7400
|View full text |Cite
|
Sign up to set email alerts
|

LPS-induced downregulation of microRNA-204/211 upregulates and stabilizes Angiopoietin-1 mRNA in EA.hy926 endothelial cells

Abstract: Angiopoietin-1 (ANG-1), a ligand of the endothelial cell-specific TIE2 surface receptor, acts in a complementary and coordinated manner with vascular endothelial growth factor during the process of angiogenesis. ANG-1 can be used as a clinically informative biomarker of disease severity and outcome in severe sepsis. The epithelium-specific Ets transcription factor 1 can activate ANG-1 transcription in the setting of inflammation; however, relatively little is known about the regulation of ANG-1 by microRNAs (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Many studies have shown that miR-204-5p and miR-211 play similar roles in multiple biological processes. Melatonin or high phosphorus-induced miR-204/-211 attenuate vascular calcification and ageing in vascular smooth muscle cells. , miR-204/-211 are also involved in the process of human periodontal ligament stem cell chondrogenesis and umbilical vein endothelial cells angiogenesis . miR-204/-211 increase cellular growth and proliferation in breast cancer and melanoma by downregulating tumor suppressor genes.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that miR-204-5p and miR-211 play similar roles in multiple biological processes. Melatonin or high phosphorus-induced miR-204/-211 attenuate vascular calcification and ageing in vascular smooth muscle cells. , miR-204/-211 are also involved in the process of human periodontal ligament stem cell chondrogenesis and umbilical vein endothelial cells angiogenesis . miR-204/-211 increase cellular growth and proliferation in breast cancer and melanoma by downregulating tumor suppressor genes.…”
Section: Discussionmentioning
confidence: 99%
“…The role of miR-211-5p has not been well-studied in sepsis, but it has been implicated as a regulator of a variety of cellular processing including angiogenesis [ 18 ], maintenance of joint homeostasis [ 19 ], and autophagy-dependent apoptosis [ 20 ]. miR-211 has recently been proposed to play a role in sepsis modulation [ 21 ] as there is some evidence that miR-211 levels drop after exposure to LPS in cell culture [ 22 ] and that miR-211 could protect against inflammation in osteoarthritis [ 23 ]. In our study, miR-211 was upregulated in umbilical cord blood plasma, but not in the umbilical cord tissue.…”
Section: Discussionmentioning
confidence: 99%
“…HULC plays an oncogene role in a variety of cancers [25,26], and a recent report revealed that increased HULC expression was related to LPS-induced inflammatory response and sepsis in endothelial cells [27]. Recently, the role of miR-204-5p in sepsis has been gradually explored, and it could target ANG-1 and be targeted by lncRNA NEAT1 to inhibit the damage of LPS on cells [28,29]. LncRNA generally functions as ceRNA of miRNA to regulate mRNA expression [30].…”
Section: Discussionmentioning
confidence: 99%